THE ERADICATION OF CORRUPTION AND THE ENFORCEMENT OF THE LAW IN INDONESIA AS SEEN THROUGH THE LENS OF LEGAL PHILOSOPHY - Dany Try Hutama Hutabarat; Egi Delardi; Ade Irwansyah; Donni Bascara; Bayu Ansori; Faisal Tanjung; Samdoni Jarwal Sinaga; Muhammad Tuah; Rizki Adrian; Agus Budi; Annisya Raya Tanjung; Nurcahaya Nurcahaya; Dinda Ayu Mahvira; Vivi Melvita Sari; Ahmad Helmisyam Silitonga (Transpublika Publisher, 2022)
Corruption is a product of the attitude of life of a group of people who use money as a standard of truth and as absolute power. Corruption has been going on for a long time, since the times of Ancient Egypt, Babylonia, Rome until the Middle Ages and until now. The purpose of this study is to determine the eradication of corruption and law enforcement in terms of the perspective of legal philosophy as a philosophy of implementing positive law in Indonesia. This study is normative legal research with descriptive method which explains that this legal research is carried out using primary legal materials, secondary legal materials and tertiary legal materials. Philosophy of Law which is the basic foundation of thinking in the application of any applicable legal rules and is considered in many branches of science gets special attention on the enforcement of corruption which should be done in eradicating corruption so that enforcement is not only based on written rules alone in eradicating but the eradication of corruption animates law enforcement in enforcement of corruption, written laws can be regulated, but these rules can be implemented by the implementers so that when the rules apply at the time of a criminal act of corruption, they can be in line with what has been written in the laws and regulations.